2015
DOI: 10.1186/s40557-015-0065-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of applying ethnicity-specific spirometric reference equations to Asian migrant workers in Korea

Abstract: ObjectivesAsian migrant workers in Korea have various ethnicities. The purpose of this study was to evaluate the difference in spirometric interpretation made using the set of third National Health and Nutrition Examination Survey (NHANES III) reference equations and the relevant ethnicity-specific reference sets.MethodsSpirometry was performed on 166 migrant and 498 Korean male workers between March and November 2012. We analyzed the spirometric data of healthy never-smokers. Spirometric patterns were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Most notably, patients with African and Southeast Asian ancestry are expected to have smaller lungs than Caucasians, Latinos, and patients with North Asian (e.g., North China, Korea) ancestry [19]. As an example, Kim et al [20] showed that in healthy nonsmokers, 30% of Southeast Asians had abnormal lung function when a reference equation that did not account for race was utilized.…”
Section: Pretest Proceduresmentioning
confidence: 99%
“…Most notably, patients with African and Southeast Asian ancestry are expected to have smaller lungs than Caucasians, Latinos, and patients with North Asian (e.g., North China, Korea) ancestry [19]. As an example, Kim et al [20] showed that in healthy nonsmokers, 30% of Southeast Asians had abnormal lung function when a reference equation that did not account for race was utilized.…”
Section: Pretest Proceduresmentioning
confidence: 99%
“…7,8 The fact that the incidence of tracheostomy was larger in a group does not mean greater efficiency in predicting extubation failure or success: The decision to perform tracheotomy includes several issues, like consciousness level, underlying medical conditions, and etiology of respiratory failure. 9 Therefore, Mathews et al share our conclusions, that proportional assist ventilation plus is a safe method and is efficient to perform a spontaneous breathing trial, comparable with other existing methods (T-tube and pressure support ventilation), and a clinical option for clinicians and respiratory practitioners in the ICU.…”
Section: In Replymentioning
confidence: 99%
“…Defining the presence of moderate airway obstruction as an FEV 1 Ͻ80% has been shown to misclassify subjects because of age, sex, and ethnicity biases, depending on the reference equations chosen. 7 Kim et al 8 showed that applying the third National Health and Nutrition Examination Survey (NHANES III) FEV 1 reference equations to Asians misclassified 30% of never-smokers when compared with an ethnically specific equation.…”
Section: Erica F Osaku Pt Phdmentioning
confidence: 99%